Survey and monitoring of pests, parasites and predators of pulse crops in central and eastern Uttar Pradesh (The Journal of Plant Protection Sciences, 2020)
A survey was conducted in chickpea, pigeonpea, and lentil crops in different districts of Uttar Pradesh. A total of 22 districts were surveyed to record gram pod borer Helicoverpa armigera, Bihar hairy caterpillar Spilarctia obliqua, plant hopper of Pentatomorpha group, termite Odontotermes spp., and cutworm Agrotis ipsilon in chickpea, whereas Campoletis chlorlidae was recorded as a natural enemy feeding on H. armigera larvae.
Keywords: Chick pea; pigeonpea; lentil; Helicoverpa armigera; parasite; predator